Women Participation in Rural Tourism: A Case of Ella, Sri Lanka - Rasanjali, Chamika; Sivashankar, Pathmanathan; Mahaliyanaarachchi, Rohana P. (Universitas Muhammadiyah Yogyakarta, 2021)
Tourism industry is one of sectors that have potential to develop and grow in the next few years in Sri Lanka. According to Tourism Development Strategy of Sri Lanka, tourism industry is expected to be the largest foreign exchange earner by 2024. The principal focus of this study was to explore major factors that affect women’s participation and non-participation in the hospitality industry in Ella DS division Sri Lanka. The study used a deductive approach, and primary data were collected through a self-administered structured questionnaire. Samples were 60 women, consisting of thirty women involved in the hospitality industry and thirty women of the non-hospitality industry, randomly selected. Results were analyzed using descriptive statistics and inferential statistics. The results found that the differences in language skills and problem-solving had the most significant effect on women’s participation in hospitality industry. Besides, childcare responsibility and lack of experience were affected women’s involvement in this industry. The results also showed that most of the non-hospitality workers have language barriers (33.3%), lack of knowledge about tourism industry (23.3%), and lack of opportunities to engage in tourism work (13.3%). Based on the results, 53.3% of 30 non-hospitality workers had an idea to be involved in tourism and hospitality industry in the future, while the remaining 46.6% had no idea to be involved.